Analisis kualitas air sungai berdasarkan ketinggian sungai Bladak dan Sungai Kedungrawis di Kabupaten Blitar - Pingki, Tamara; ., Sudarti (e-Journal BUDIDAYA PERAIRAN, 2021)
The purpose of this study was to analyze the quality of river water based on differences in height, namely in rivers with an altitude of Â± 349 in Nglegok District and rivers with an altitude of Â± 252 in Kademangan District, Blitar Regency. Measurement of river water brightness using Sechhi Disk. Measurement of temperature, pH and TDS is carried out by measuring river water samples taken. Based on the data analysis that has been carried out and explained, the quality of river water will be inversely proportional to the temperature and TDS value. Meanwhile, the quality of river water is directly proportional to the brightness and pH. The water temperature in the Bladak River is cooler or lower than the water temperature in the Kedungrawis River. The water in the Bladak River is brighter than the water in the Kedungrawis River. The pH of the water in the Bladak River is higher or more alkaline than the pH of the water in the Kedungrawis River. The Total Dissolved Solid (TDS) value in the Bladak River is smaller than the TDS value in the Kedungrawis River